Margarita Karamichova (ed.): Gradivo za etnologojata na migraciite. Sbornik studii.: Etnografický institut s muzeem BAN, Sofia 2006, 256 s. - Jakoubek, Marek (Lidé města, 2008)
A review of the book by Margarita Karamichova.